PENGARUH BRAND IMAGE TERHADAP KEPUTUSAN PEMBELI SIMCARD TELKOMSEL PADA MAHASISWA FISPOL UNSRAT MANADO - Sakul, Octavia Inggrid; Tampi, Johny; Tumbel, Tinneke (Sam Ratulangi University, 2017)
The purpose of this research is to determine the influence of brand image oncostumer purchase decision of Telkomsel sim card. This is an associative quantitativeresearch with survey method to collect the data. The population in this research was allstudent at Faculty of Social and Political Science Sam Ratulangi Manado. Sample sizewas selected using slovin formula with total 100 respondents, and analyzed usingcorrelation analysis and simple linier regression. The result revealed that brand imagehad an impact on consumer purchase decision of Telkomsel sim card. This resultrecommends the company to understand the characteristics can be more reflected thebrand image of the costumer. So the more company make the brand image better, themore consumer wull be interested to use the products in that company.